(untitled) (Research, Society and Development, 2019)
The use of medicinal plants in the prevention and therapeutics of diseases has been carried out for a long time. Phytotherapeutic treatment is also applied in androgenetic alopecia, which is a condition characterized by hair loss and affects individuals of both sexes, with a higher prevalence in men. The objective of the article is to present the results of a bibliographical research related to the effectiveness of phytotherapy in the treatment of androgenetic alopecia. It is a literature review of the integrative type, for the construction of the research, was used of articles available in the following databases: PUBMED and ScienceDirect. After selection and analysis of the data obtained through reading, it was observed the use of several types of phytotherapics in the treatment of androgenic alopecia. The researches showed results with a positive effect of the use of this treatment on the hair growth of the individuals studied, with better resistance and increase of hair of the anagen phase.